2008
DOI: 10.1007/s10823-008-9060-z
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Self-care among a Multiethnic Sample of Older Adults

Abstract: Type 2 diabetes constitutes a leading and increasing cause of morbidity and mortality among older adults, particularly African Americans, Native Americans, Mexican Americans, and rural dwellers. To understand diabetes self-care, an essential determinant of diabetic and overall health outcomes, 80 middle aged and older adults from these four disproportionately affected racial/ ethnic/residential groups engaged in in-depth interviews, focusing on approaches to and explanations for diabetes self-care. Certain sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 36 publications
2
41
1
Order By: Relevance
“…Schoenberg et al . () found in a multi‐ethnic sample of US adults with diabetes that respect and trust in authority of physicians was also deemed to be high as participants’ quotes were linked to conventional self‐care approaches to lifestyle modifications. It is unclear if the similarities are due to management of a chronic condition or ethnicity, and further research would need to investigate this particular area.…”
Section: Discussionmentioning
confidence: 99%
“…Schoenberg et al . () found in a multi‐ethnic sample of US adults with diabetes that respect and trust in authority of physicians was also deemed to be high as participants’ quotes were linked to conventional self‐care approaches to lifestyle modifications. It is unclear if the similarities are due to management of a chronic condition or ethnicity, and further research would need to investigate this particular area.…”
Section: Discussionmentioning
confidence: 99%
“…Health disparities in the treatment and management of type‐2 diabetes occur nationwide, but rural communities are disproportionately impacted. One major reason is that rural populations tend to encompass a large proportion of ethnically diverse cultures including non‐Latino whites, Latinos, African Americans, and Native Americans (Schoenberg, Traywick, Jacobs‐Lawson, & Kart, ). Within this diversity is the use of complementary and alternative medicine options that include herbal remedies, dietary remedies, teas, and spiritual interventions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Symptom awareness can also signal a person to implement specific health care practices [810]. Previous studies have reported that older individuals’ diabetes symptom interpretation may differ between age groups [11,12].…”
Section: Introductionmentioning
confidence: 99%